Comparative Morphology and Anatomy of Few Mangrove Species in Sundarbans, West Bengal, India and its Adaptation to Saline Habitat - Rodriguez, Humberto Gonzalez; Mondal, Bholanath; Sarkar, N. C.; Ramaswamy, A.; Rajkumar, D.; Maiti, R. K. (International Journal of Bio-resource and Stress Management, 2023)
Mangroves cover large areas of shoreline in the tropics and subtropics where they are important components in the productivity and integrity of their ecosystems. High variability is observed among the families of mangroves. Structural adaptations include pneumatophores, thick leaves, aerenhyma in root helps in surviving under flooded saline conditions. There is major inter- and intraspecific variability among mangroves. In this paper described morpho-anatomical characters helps in identification of family and genus and species of mangroves. Most of the genus have special type of roots which include Support roots of Rhizophora, Pnematophores of Avicennia, Sonneratia, Knee roots of Bruguiera, Ceriops, Buttress roots of Xylocarpus. Morpho-anatomically the leaves show xerophytic characteristics. This morphological and anatomical response to local conditions may allow the trees to maximize their photosynthetic efficiency Most of the species are now endangered species due to environmental effects and human activities.